Local Analyst Earnings Forecast Advantages in Europe - Orpurt, Steven Francis (Institutional Knowledge at Singapore Management University, 2004)
Local analysts may be in an advantageous earnings forecast position relative to non-local analysts due to information asymmetries, different incentives or lower information search costs. Alternatively, local managers may manage earnings towards local analyst earnings forecasts. Supporting these conjectures, I find that local analysts issue more accurate, timelier earnings forecasts than non-local analysts. Germany and the Netherlands offer the strongest evidence. Evidence is inconclusive in Belgium and Switzerland. In no country is there evidence of non-local analyst forecasting advantages. U.K. (London) based analysts are less accurate forecasters than competing analysts. The magnitude of the local forecast advantage is large enough to be economically intersesting. These findings are indicative of geographic information asymmetries and support explanations for equity home bias.